EROI Analysis for Direct Coal Liquefaction without and with CCS: The Case of the Shenhua DCL Project in China - Zhaoyang Kong (Energies, 2015)
Currently, there are considerable discrepancies between China’s central government and some local governments in attitudes towards coal to liquids (CTL) technology. Energy return on investment (EROI) analysis of CTL could provide new insights that may help solve this dilemma. Unfortunately, there has been little research on this topic; this paper therefore analyses the EROI of China’s Shenhua Group Direct Coal Liquefaction (DCL) project, currently the only DCL commercial project in the world. The inclusion or omission of internal energy and by-products is controversial. The results show that the EROIstnd without by-product and with internal energy is 0.68–0.81; the EROIstnd (the standard EROI) without by-product and without internal energy is 3.70–5.53; the EROIstnd with by-product and with internal energy is 0.76–0.90; the EROIstnd with by-product and without internal energy is 4.13–6.14. Furthermore, it is necessary to consider carbon capture and storage (CCS) as a means to control the CO2 emissions. Considering the added energy inputs of CCS at the plant level, the EROIs decrease to 0.65–0.77, 2.87–3.97, 0.72–0.85, and 3.20–4.40, respectively. The extremely low, even negative, net energy, which may be due to high investments in infrastructure and low conversion efficiency, suggests CTL is not a good choice to replace conventional energy sources, and thus, Chinese government should be prudent when developing it.